Detection of Campylobacter jejuni and Campylobacter coli by a PCR assay in Patients with Diarrhea - Rawa Abdalkreem Abd; Ezat Hussain Mezal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Campylobacter sp. is complex taxonomy, fastidious growth criteria, and biochemical inertness, identificationof campylobacter in clinical samples by traditional cultures is problematic and slow. Because of that a rapid,responsive, and precise polymerase chain reaction (PCR) assay capable of detecting and differentiatingCampylobacter jejuni (hipO) and Campylobacter coli (glyA) directly from human feces. Diagnostic PCRon template DNA extracted directly from the stool offers catchy advantages including the reduced time ofanalysis and detection of non-viable and non-cultivable bacteria contained in the sample.From a humanpatient with diarrhea by using conventional PCR assay. One hundred fecal samples were collected frompatients suffering from watery, bloody, and mucous diarrhea, aged (1 month-60 years old) from both sexes(55Male, 45 Female). From many places in Thi-Qar province, Bint Alhuda Hospital, and Outpatient Clinicsduring the period from August 2020 to November 2020. Four isolates (4%) were diagnosed as genus C.coliand one isolate (1%) was diagnosed as genus C.jejuniby using glyA and hipO gene for C.coli and C.jejunirespectively.